2014
DOI: 10.1089/ars.2013.5322
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tumor Cell Apoptosis by a Proteasome Deubiquitinase Inhibitor Is Associated with Oxidative Stress

Abstract: Our data show that enhanced oxidative stress and ER stress are major determinants of the strong apoptotic response elicited by the 19S DUB inhibitor b-AP15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 66 publications
(96 reference statements)
13
82
1
Order By: Relevance
“…Blocking of proteasome function is known to induce the expression of a cellular chaperone response, induction of ER stress and oxidative stress (8,3033). Microarray analysis showed that VLX1570 induces chaperone expression (HSPA6, HSPA1L, HSPA4L), the oxidative stress marker HMOX1 [known to be induced by bortezomib (34)], and the ER stress-associated marker DDIT3/CHOP in MCF7 cancer cells (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Blocking of proteasome function is known to induce the expression of a cellular chaperone response, induction of ER stress and oxidative stress (8,3033). Microarray analysis showed that VLX1570 induces chaperone expression (HSPA6, HSPA1L, HSPA4L), the oxidative stress marker HMOX1 [known to be induced by bortezomib (34)], and the ER stress-associated marker DDIT3/CHOP in MCF7 cancer cells (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that USP14 and UCHL5 belong to different classes of DUBs, dual inhibition of these enzymes by small molecules would a priori be expected to be possible only in the context of broad-spectrum DUB inhibition. Recently however, a number of compounds have been described that preferentially inhibit proteasomal DUB activity compared to other cytosolic that also inhibits proteasomal deubiquitinase activity resulting in a similar stress response and cytotoxicity profile (Brnjic et al, 2014;Coughlin et al, 2014). Another pair of structurally related compounds, G5 and F6, initially identified in a screen for agents that induce apoptosis Bcl-2 over-expressing cells; were subsequently shown to be potent inhibitors of general DUB activity leading to acute proteotoxic stress and apoptosis (Aleo et al, 2006).…”
Section: Proteasomal Dubs As Drug Targets For Cancer Therapymentioning
confidence: 99%
“…This difference in synergy observed is presumably due to the irreversible binding of carfilzomib to the proteasome compared to the slowly reversible nature of bortezomib. sufficient to perturb bortezomib-induced apoptosis (Brnjic et al, 2014;D'Arcy et al, 2011).…”
Section: Mechanisms Of Resistance To Bortezomib and Other Inhibitors mentioning
confidence: 99%
“…These results demonstrate that AgDT-triggered DUB inhibition is not dependent on ROS production. It has been believed that generation of cellular ROS is associated with proteasome inhibitorinduced cell death [41,42]. Proteasome inhibition leads to accumulation of misfolded proteins in the endoplasmic reticulum (ER) and thereby induces ER stress, which may cause the accumulation of ROS [43,44].…”
Section: Discussionmentioning
confidence: 99%